The broadcast of shared attention and its impact on political persuasion. [article]. - Shteynberg, Garriy
In democracies where multitudes yield political influence, so does broadcast media that reaches those multitudes. However, broadcast media may not be powerful simply because it reaches a certain audience, but because each of the recipients is aware of that fact. That is, watching broadcast media can evoke a state of shared attention, or the perception of simultaneous coattention with others. Whereas past research has investigated the effects of shared attention with a few socially close others (i.e., friends, acquaintances, minimal ingroup members), we examine the impact of shared attention with a multitude of unfamiliar others in the context of televised broadcasting. In this paper, we explore whether shared attention increases the psychological impact of televised political speeches, and whether fewer numbers of coattending others diminishes this effect. Five studies investigate whether the perception of simultaneous coattention, or shared attention, on a mass broadcasted political speech leads to more extreme judgments. The results indicate that the perception of synchronous coattention (as compared with coattending asynchronously and attending alone) renders persuasive speeches more persuasive, and unpersuasive speeches more unpersuasive. We also find that recall memory for the content of the speech mediates the effect of shared attention on political persuasion. The results are consistent with the notion that shared attention on mass broadcasted information results in deeper processing of the content, rendering judgments more extreme. In all, our findings imply that shared attention is a cognitive capacity that supports large-scale social coordination, where multitudes of people can cognitively prioritize simultaneously coattended information. -- (from the authors)
Keywords: Judgment polarization; Mass media; Political persuasion